Caloric restriction impacts skin barrier function and attenuates the development of hyperplasia skin disease - Tang, Huihao; Li, Jianzhou; Jin, Mengyu; Li, Chengliang; Zhai, Chuntao; Wang, Juan; Huang, Taomin; Ding, Xiaolei (Frontiers in Nutrition, 2024)
Caloric restriction (CR) stands out as one of the most potent interventions that prolong lifespan and mitigate age-associated diseases. Despite its well-established systemic effects, the impact of CR on skin physiological function remains poorly understood, and whether the intervention can alleviate the progression of inflammatory skin diseases remains uncertain. Here, we investigated the effects of CR on mouse skin barrier function and inflammatory response. Our results revealed that CR led to dramatic atrophy in the skin subcutaneous layer. The expression of barrier proteins and trans-epidermal water loss remain largely unchanged. Intriguingly, skin from CR mice exhibited reduced expression of inflammatory cytokines under steady conditions. In an imiquimod (IMQ)-induced mouse model of psoriasis, CR treatment attenuated the pathogenesis of psoriasis phenotypes, accompanied by a reduced activation of mTOR signaling in the psoriatic skin. Taken together, our findings shed light on the complex interplay between metabolic interventions and skin health, suggesting that CR has the potential to serve as a modulator of inflammatory responses in the skin.